Analisis Mediasi Perencanaan Tim Kerja Dosen pada Pengaruh Team efficacy dan Iklim Keamanan Psikologis terhadap Kinerja Tim - Riyanto Riyanto; Masduki Asbari; Multi Nadeak; Dewiana Novitasari (University of Merdeka Malang, 2021)
Based on social cognitive theory (SCT), this study postulates team characteristics and environmental factors as the main drivers of team performance. In the proposed model of this study, team performance was positively and significantly influenced by two predictors (ie, team efficacy and psychological safety climate). Likewise, work team planning has a positive and significant effect on team performance. Data were collected from 107 questionnaires returned from samples taken by random sampling from lecturers at five private universities in Jakarta. Data were analyzed using SEM method with SmartPLS 3.0 software. The results of this study indicate that team efficacy and psychological safety climate have a positive and significant effect on team work planning and team performance. Likewise, work team planning has a positive and significant effect on team performance. In addition, empirical testing of this study, by investigating lecturers at private universities in Jakarta, complements the application of social cognitive theory in understanding team performance. Finally, the managerial implications of team performance and open problems for future studies are discussed at the end of the research report.